2020
DOI: 10.1159/000509787
|View full text |Cite
|
Sign up to set email alerts
|

Association between Satisfaction with Dialysis Treatment and Quality of Life: A Cross-Sectional Study

Abstract: Introduction: CKD is associated with a reduction of patients’ health-related quality of life. Considering the time spent in dialysis, satisfaction with care is essential for patients QOL. Objective: Since the possible association between satisfaction with the dialysis care and QOL has never been studied, in this study, we explore this plausible link. Methods: One hundred three patients on hemodialysis (HD) and peritoneal dialysis (PD) filled-in patient-reported outcome measures (PROMs) and patient-reported exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…One study examining satisfaction with dialysis treatment and QOL revealed that communication between the care provider and the patients plays a favorable role for the QOL. 24 Test separately study of KDQOL-SF subscales toward the patients over or under 66-yrs old showed aging related vulnerability for sudden change of surrounding circumstances.…”
Section: Discussionmentioning
confidence: 97%
“…One study examining satisfaction with dialysis treatment and QOL revealed that communication between the care provider and the patients plays a favorable role for the QOL. 24 Test separately study of KDQOL-SF subscales toward the patients over or under 66-yrs old showed aging related vulnerability for sudden change of surrounding circumstances.…”
Section: Discussionmentioning
confidence: 97%
“…In other words, patient-centered care has good results on the health outcomes of patients. Patient’s satisfaction with care had a good effect on health outcomes [ 14 , 15 ], and effective communication would have helped the patient’s decision-making about treatment as a result. Several studies [ 16 , 17 ] suggest that decision coaching in conjunction with decision aids may be effective in increasing decision-making participation, increasing knowledge, aligning decisions with patient values, and reducing decision-making conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…This high level of satisfaction with staff is aligned with other HD cohorts in Lebanon [ 23 ]. There is a clear relationship between the care satisfaction and quality of life of dialysis patients, making the healthy interaction between the patient and health care providers crucial in any dialysis unit [ 24 ]. Another essential factor that plays a significant role in HD patients’ psychology is social support [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%